Wired/Wireless Internet Communications 14th IFIP WG 6.2 International Conference, WWIC 2016, Thessaloniki, Greece, May 25-27, 2016, Proceedings - Mamatas, Lefteris; Matta, Ibrahim; Papadimitriou, Panagiotis; Koucheryavy, Yevgeni; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book constitutes the refereed proceedings of the 14th IFIP WG 6.2 International Conference on Wired/Wireless Internet Communications, WWIC 2016, held in Thessaloniki, Greece, in May 2016. The 27 papers presented in this volume were carefully reviewed and selected from 54 submissions. The topics addressed are: wireless technologies and systems, middleboxes and addressing, energy efficiency, network applications and tools, network protocols, network modeling, wireless sensor networks, and resource management and optimization.
High-Performance Wideband SDR Channelizers -- Location Based Transmission Using a Neighbour Aware-Cross Layer MAC for Ad Hoc Networks -- Message Transmission Scheduling on Tandem Multi-hop Lossy Wireless Links -- Influence of Backoff Period in Slotted CSMA/CA of IEEE 802.15.4 -- Multipath TCP Proxy: Unshackling Network Nodes from Today's End-to-End Connection Principle -- SDN-based Source Routing for Scalable Service Chaining in Datacenters -- An Efficient Geographical Addressing Scheme for the Internet -- On the Energy Inefficiency of MPTCP for Mobile Computing -- Energy for Mobile Devices: A (3y(BStore and Rendezvous(3y (BApproach -- Data Aware Communication for Energy Harvesting Sensor Networks -- Scalability of Passive and Active Solutions for Time-Based Ranging in IEEE 802.11 Networks -- A Collaborative Video Download Application Based on Wi-Fi Direct -- Human-in-the-Loop Connectivity Management in Smartphones -- Hardware MIMO Channel Simulator for Cooperative & Heterogeneous 5G Networks with VLC Signals -- Improving Spatial Indexing and Searching for Location-Based DNS Queries -- QoS Multi-tree Based Routing Protocol for Inter-Mesh Infrastructure Communications -- A Variable-Length Network Encoding Protocol for Big Genomic Data -- On the Evolution of Complex Network Topology under Network Churn -- A Reputation-Based Coalition Game to Prevent Smart Insider Jamming Attacks in MANETs -- A Goodness Based Vertical Handoff Algorithm for Heterogeneous Networks -- Routing-Aware Time Slot Allocation Heuristics in Contention-Free Sensor Networks -- System Design and Analysis of UAV-Assisted BLE Wireless Sensor Systems -- Implementing a Broadcast Storm Attack on a Mission-Critical Wireless Sensor Network -- Critical Sensor Density for Event-Driven Data-Gathering in Delay and Lifetime Constrained WSN -- Effective Capacity in Broadcast Channels with Arbitrary Inputs -- Throughput Improvement Using Partially Overlapping Channels in WLAN with Heterogeneous Clients -- Optimal Link Deployment for Minimizing Average Path Length in Chain Networks.s
Keywords: Computer science; Computer communication systems; Computer system failures; Software engineering; Algorithms; Information storage and retrieval; Computer Science; Computer Communication Networks; Information Systems Applications (incl. Internet).; Software Engineering; Algorithm Analysis and Problem Complexity; System Performance and Evaluation; Information Storage and Retrieval; Electronic books